(untitled) (Medico Legal Update, 2021)
The neogenic recombinases are potentially a source of genetic variability possibly implicated in the mechanisms of genetic instability involved in the processes of carcinogenesis. One of these neogenic recombinases is the nuclear apoptosis-inducing factor 1(NAIF1), which codes the protein NAIF1 that induces apoptosis in various human cancers. The aim of this work is to study the expression of NAIF1 neogene in cancerous and non-cancerous colorectal tissues. The protein expression of NAIF1gene has been studied by western blot method in the samples of protein extracted from 29 patients with colorectal cancer. The result of this study showed that the protein expression of NAIF1 was found in both cancerous and non-cancerous colorectal tissues, but it is highly expressed in non-cancerous tissues adjacent to cancerous one. Its expression is higher in non-metastatic cancerous tissues compared with metastatic one. Also this expression is higher in microsatellite instable (MSI) group of cancer compared with microsatellite stable (MSS) group. It can be concluded that NAIF1 protein expression inversely related with more advanced stage or grade of colorectal cancer and it may have a role in inhibition of proliferation, migration and invasion of colorectal cancer by inducing apoptosis.